Industrial Transition at the Border: A Qualitative Inquiry into Workforce Adaptation and Institutional Collaboration in Batam City - Timbul Dompak; Karol Teovani Lodan; Risman Sarifudin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to examine how Batam City—located at Indonesia’s international border and functioning as a free-trade industrial zone—navigates its ongoing industrial transition and how this transformation influences workforce adaptation and inter-institutional collaboration. The study also wanted to find out how government agencies, businesses, and training centers see the problems that come up when investment patterns change, automation happens, and labor needs change. By concentrating on this aspect, the study offers a comprehensive insight into the governance dynamics influencing industrial resilience in Batam. Materials and methods. This study utilized a qualitative case study methodology. Data were collected via semi-structured in-depth interviews with officials from local government agencies, representatives from the manufacturing and service sectors, instructors from vocational training schools, and workers undergoing industrial transformation. Results. The results show three main themes: (1) workforce adaptation is still uneven because of skill mismatches and a lack of opportunities to learn new skills; (2) institutional collaboration is difficult because of broken coordination, overlapping mandates, and policies that don't always match; and (3) even though these problems exist, new informal networks and partnerships across sectors show promise for improving Batam's ability to adapt during industrial transition. Conclusions. The study finds that Batam's industrial transformation needs not only better ways to improve workers' skills but also stronger and more formal ways for people to work together to make decisions. To make the economy in a border region more resilient, encourage industrial upgrading, and ensure long-term growth, it is important to strengthen cooperation between public institutions, industries, and training centers.